2015
DOI: 10.1183/09031936.00080014
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-1-phosphate inhibits cigarette smoke-induced airway inflammation

Abstract: Sphingolipids are involved in the pathogenesis of inflammatory diseases. The central molecule is ceramide, which can be converted into ceramide-1-phosphate (C1P). Although C1P can exert anti-and pro-inflammatory effects, its influence on cigarette smoke (CS)-induced lung inflammation is unknown. We aimed to clarify the role of C1P in the pathogenesis of CS-triggered pulmonary inflammation and emphysema in humans and mice.The effects of C1P were addressed on CS-induced lung inflammation in C57BL/6 mice, CS extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…In our previous study, we already described only an anti-inflammatory effect until a C1P concentration of 10 μM (51), which is in line with the results of Hankins et al (18). Often a proinflammatory effect of C1P (14, 52) is described either with higher C1P concentrations or different solvent (53, 54).…”
Section: Discussionsupporting
confidence: 90%
“…In our previous study, we already described only an anti-inflammatory effect until a C1P concentration of 10 μM (51), which is in line with the results of Hankins et al (18). Often a proinflammatory effect of C1P (14, 52) is described either with higher C1P concentrations or different solvent (53, 54).…”
Section: Discussionsupporting
confidence: 90%
“…The lab of Gómez-Muñoz has previously demonstrated that C1P prevents apoptosis in macrophages by inhibition of acid SMase activity, resulting in reduced levels of the pro-apoptotic ceramide [9]. A recent report showed that C1P can reduce cigarette smoke-induced lung inflammation, apparently by inhibiting cigarette smoke-induced activation of neutral SMase and NFκB and subsequent pro-inflammatory cytokine release in neutrophils [47]. In relation to these findings, a synthetic C1P analog, named SMA-7, suppressed LPS-stimulated NFκB activation and pro-inflammatory cytokines release from intestinal epithelial cells and from human THP-1 macrophages, by inhibiting LPS-stimulated ceramide production through neutral and acid SMase, respectively [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory potential of C1P is particularly relevant in the lung where it was shown to inhibit acute and chronic inflammation and development of emphysema. These actions required reduction of pro-inflammatory cytokines and inhibition of SMase and NF-kB activities in inflamed lung tissue (Baudiss et al 2015).…”
Section: Role Of Ceramide Kinase/c1p In Inflammationmentioning
confidence: 99%